Fatal and Nonfatal Rip Saw Injuries - Handlosová, Klára; Klabal, Ondřej; Dokoupil, Marek; Vojtek, Vladimír; Uvíra, Matěj; Handlos, Petr (Journal of forensic sciences, 2020)
This paper deals with a fatal stab wound suffered by a 29-year-old man and nonfatal injuries of 35-year-old and 67-year-old saw operators. Rip saw is a machine that is specially designed for making a rip cut, a cut made parallel to the direction of the wood grain. Rip-saw-related injuries mostly occur when a person is struck by the cutting material, which usually involves splinters of irregular shape and diameter. When the splinter strikes the body diagonally, the injuries may include abrasions, lacerations, and cut wounds; in situations where the victim is struck directly, the most common injuries are oval- or star-shaped stab wounds with a varying width of abrasions around the wounds. Therefore, such injuries may come across as injuries produced by a knife-like instrument, which is an added difficulty in the interpretation of such injuries.
Keywords: dospělí; Accidents, Occupational; pracovní nehody; bodné rány; Heart Injuries; homicide; fibula; Adult; Tomography, X-Ray Computed; fraktury tibie; suicide; lidé; tříštivé fraktury; Tibial Fractures; forensic pathology; poranění ruky; Wounds, Stab; Humans; Fibula; Male; Aged; poranění srdce; Fractures, Comminuted; accidental death; Thoracic Injuries; sharp force injuries; senioři; mužské pohlaví; rip saw; Hand Injuries; poranění hrudníku; stab wounds; počítačová rentgenová tomografie